1971
DOI: 10.1063/1.1660455
|View full text |Cite
|
Sign up to set email alerts
|

Nonstoichiometry and Crystal Growth of Lithium Niobate

Abstract: Deviations from stoichiometry occurring during the crystal growth of lithium niobate have been studied by 93Nb NMR and by shifts in the ferroelectric transition temperature. The high-temperature phase equilibria of nonstoichiometric lithium niobate were accurately determined by these techniques together with DTA and crystal-growth experiments. The congruently melting composition is located at 48.6 mole% Li2O and the solid-solution region at room temperature extends from 48% to 50% Li2O. The implications of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
95
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 332 publications
(99 citation statements)
references
References 26 publications
4
95
0
Order By: Relevance
“…Peterson 1 and Carruthers et al 2 found that stoichiometric crystals could be pulled only from strongly off-stoichiometric melts with $58.0 mol. % Li 2 O content and even those crystals were small and/or of inferior quality.…”
Section: Growth Of Stoichiometric Linbo 3 a Early Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Peterson 1 and Carruthers et al 2 found that stoichiometric crystals could be pulled only from strongly off-stoichiometric melts with $58.0 mol. % Li 2 O content and even those crystals were small and/or of inferior quality.…”
Section: Growth Of Stoichiometric Linbo 3 a Early Workmentioning
confidence: 99%
“…Peterson 1 and Carruthers et al 2 found that stoichiometric crystals could be pulled only from strongly off-stoichiometric melts with $58.0 mol. % Li 2 O content and even those crystals were small and/or of inferior quality. Based on detailed investigations of the phase diagram of the Li 2 O-Nb 2 O 5 binary system, Byer et al 3 grew high quality LN crystals, thereby locating the congruently melting composition of LiNbO 3 at 48.6 mol.…”
Section: Growth Of Stoichiometric Linbo 3 a Early Workmentioning
confidence: 99%
See 3 more Smart Citations